A plan for improving The City Of Cape Town Corporate Intranet by applying knowledge sharing Insights - Evans, Herbert (Library and Information Studies Centre (LISC), 2024)
Corporate intranets are an essential technology used by organisations to manage their digital information resources. An effective intranet service must balance the resource requirements of its users with the restrictions of the corporate network as well as coordinate an effective digital information storage and retrieval service. In addition, intranets typically also provide an internal communication channel and serve as a key vehicle for the corporate culture of the organisation. The City of Cape Town municipality's existing intranet platform is in the process of being migrated to more modern technology, allowing for the redevelopment of key functions including the underlying information architecture, associated site navigation elements, search and site metadata, inter alia. As a member of the intranet's custodian department, the researcher is well positioned to conduct a study of the existing intranet service offering, and to offer an assessment of improvements needed to meet the needs of the modern digital workplace. The research study examines the role of the corporate intranet as a Knowledge Management (KM) tool, with a focus on iterative improvement by the application of an action research approach. Key areas that are examined include the performance, configuration and management of the network infrastructure; site content management; intranet site structure and design; site navigation; site search and search results performance; the application of site governance and usage policies; the expression of corporate culture through the intranet service; the role of the intranet as a collaboration platform; and the requirements of the modern digital workplace in respect of key services including information retrieval and collaborative tools. The study's primary research data is drawn from interviews with key users of the corporate intranet via snowball sampling. The resultant qualitative data is interpreted and compared with insights from the KM literature and the researcher's own institutional knowledge, and areas of improvement are identified. The findings are to be presented to the intranet redevelopment team, and will contribute to improving the CCT corporate intranet service. The study also makes a contribution to existing research in the field of KM, Action Research case literature and intranet design theory.